Two cities on exile, history, and the imagination - Zagajewski, Adam 1945-2021 (Farrar, Strauss, Giroux, 1995)
In October 1945, when Adam Zagajewski was four months old, his family was forced to move from their beloved native city of Lvov to the ugly, industrial, and, until then, German city of Gliwice, Poland. In the evocative title essay of his new collection, Zagajewski describes his efforts to reconcile his contradictory loyalties to his family - and their idealized past - his own place and his time. In "Open Archives," Zagajewski gives the detested officials of postwar Poland their moment to explain. And finally, in the "New Little Larousse," he adds to his treasury of short, philosophical essays, mimicking encyclopedia entries, including pieces entitled "The Untold Cynicism of Poetry," "I Killed Hitler," and "The Inspired Dermatologist." Regardless of their subject, Zagajewski's essays have the subtlety and resonance of poetry: his is one of the most interesting voices in today's Europe.
Aus dem Poln übers.
Keywords: Fiktionale Darstellung; Biografie